Hole Transporting Monolayers: Self‐Assembled Hole Transporting Monolayer for Highly Efficient Perovskite Solar Cells (Adv. Energy Mater. 32/2018). Issue 32 (15th November 2018) - Magomedov, Artiom; Al‐Ashouri, Amran; Kasparavičius, Ernestas; Strazdaite, Simona; Niaura, Gediminas; Jošt, Marko; Malinauskas, Tadas; Albrecht, Steve; Getautis, Vytautas
Abstract : In article number1801892, Steve Albrecht, Vytautas Getautis and co‐workers demonstrate a novel promising concept for the formation of a hole selective monolayer in perovskite solar cells. A low temperature dopant‐free technique makes it suitable for different substrates.